2007
DOI: 10.1002/eqe.702
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of probability of collapse and design for collapse safety

Abstract: This paper illustrates a probabilistic-based methodology for quantifying the collapse potential of structural systems, which can provide us with more accurate estimates of losses induced by earthquakes. Applications of this methodology for assessment of collapse potential of existing buildings and design for collapse safety are demonstrated by equations and example. The collapse potential is represented by the probability of collapse at discrete hazard levels and on an annualized basis (mean annual frequency).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
134
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(137 citation statements)
references
References 14 publications
2
134
0
1
Order By: Relevance
“…For the aforementioned key performance measures, numerous references are available for 'closed-form' analytical solutions. The first closed-form solutions were published for the demand hazard in References [6,7], and using similar assumptions, annual frequencies of limit state exceedance and structural collapse can also be computed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the aforementioned key performance measures, numerous references are available for 'closed-form' analytical solutions. The first closed-form solutions were published for the demand hazard in References [6,7], and using similar assumptions, annual frequencies of limit state exceedance and structural collapse can also be computed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mackie and Stojadinovic [11] used closed-form solutions for damage and loss limit states to propose a PBSD approach for bridges. Zareian and Krawinkler [10] used the closed form solution for the annual rate of collapse, to propose a PBSD methodology considering structural collapse. The above three implementations also separate epistemic and aleatory uncertainties in the structural response and use the mean ground motion hazard curve.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have conducted nonlinear response history analyses of steel moment resisting frames (MacRae et al, 1990;Krawinkler, 1999, 2000;Medina and Krawinkler, 2003;Zareian and Krawinkler, 2007, Luco and Cornell, 2000, Lee and Foutch, 2000, 2002aLignos and Krawinkler, 2009). As part of the SAC project, Luco and Cornell (2000) and Lee and Foutch (2002b) assessed the effects of brittle connection fractures on the behavior of archetype steel moment resisting frame structures ranging in height from 2-to 20-stories, with pre-Northridge connections, at various levels of ground motion intensity.…”
Section: A52 Structural System Performancementioning
confidence: 99%
“…However, in this model the postcapping strength deterioration was not modeled. It has been shown both analytically Zareian and Krawinkler, 2007;Lignos and Krawinkler, 2009) and experimentally (Lignos et al, 2010(Lignos et al, , 2011dSuita et al, 2008) that the capping point is critical for assessing the collapse potential of moment resisting frames Lignos and Krawinkler, 2009;Lignos et al, 2011a). Lee and Foutch (2002a) concluded that all of the buildings with postNorthridge connections showed a high capacity-to-demand ratio ranging from 2.0 to 4.0, depending on frame configuration and height.…”
Section: A52 Structural System Performancementioning
confidence: 99%
See 1 more Smart Citation